Worth dying for : a Reacher novel - Child, Lee. (New York : Delacorte Press, 2010)
While investigating a decades-old kidnapping case, drifter Jack Reacher draws the ire of a local clan that has been terrorizing their neighbors for years. However, the clan's connection with organized crime extends far beyond rural Nebraska, giving Reacher a shot at taking down a deadly criminal enterprise.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Missing children -- Fiction; Nebraska -- Fiction